Counterfeit Luxury Goods – Effects on the Brand Image and Exclusivity Perception (International Journal of Applied Research in Management and Economics, 2024)
As counterfeits of luxury brands threaten the authenticity of genuine brands, this study considers, in the context of a quantitative analysis, the impact exposure to good and bad counterfeits has on the perception of the exclusivity and the brand image of genuine luxury brands. The monolithic concept of brand image is split into the four dimensions of quality, price, aesthetics, and tradition, which are key aspects of any luxury brand. This study contributes to the existing literature by offering a current look at the post-Covid situation regarding the impacts of counterfeiting in the luxury market in Central Europe, i.e., Germany, from a multi-faceted perspective. It establishes that for quality and aesthetics perceptions, counterfeits do not harm the brand image of genuine luxury items. In contrast, they strengthen the consumer-brand relationship. For brands, these results imply that while counterfeits decrease their profits, they also could increase brand loyalty.